UJI TEKNOLOGI BUDIDAYA TANAMAN PANGAN ORGANIK PADA KOMODITI PADI, JAGUNG DAN UBI KAYU DI DUA KAMPUNG LOKAL KABUPATEN MERAUKE - Untari Untari; Maria M.D Widiastuti; Musrifah Musrifah (Universitas Musamus, Merauke, Papua, 2017)
Organic farming systems using organic fertilizer to improve soil cekram of water needed for growth and crop production. The research objective to be achieved in this research is testing the technology cultivation of food crops from climate change impacts. Research conducted in 2015 by using the experimental method using a treated field, namely the dosing of animal organic fertilizer (0 tonnes / ha, 5 ton / ha and 10 ton / ha) in the cultivation of food crops rice plants Inpago Unsoed 1, Corn Pulut Uri and Plants Cassava conducted in Muting Village Muting District and Bupul Village Elikobel using a randomized block design. Research data analysis by using analysis statiktic tabulation and descriptive analysis using 95% confidence level. Variable field observations of variable growth and yield of rice Inpago Unsoed 1, uri sticky corn and cassava. The research concludes that the cultivation techniques by using a treatment dose of organic fertilizer on cassava, rice Inpago Unsoed 1, and cassava simultaneously significantly affect growth and crop production. Treatment dose 0 tonnes/ha lower production compared to production plants that use a higher dose is 5 tonnes/ha and 10 tonnes/ha. Maize production Pulut Uri Muting in Village each of 2.46 tonnes / ha (0 tonnes/ha), 4.36 tonnes / ha (5 tonnes/ha), and 5.8 tonnes/ha (10 tonnes/ha). Corn production in Bupul Village lower, respectively 0,8 tonnes / ha (0 tonnes/ha), 2,12 tonnes/ha (5 tonnes/ ha), and 2,49 tonnes/ha (10 tonness/ha) , whereas the effect of the use of organic fertilizer on rice growth Inpago Unsoed 1 concluded that the higher the dose of fertilizer given a positive influence on the average plant height in Muting village is 45,07 cm (10 tonnes / ha), 44,33 cm (5 tonnes/ ha), 34,43 cm (0 tonnes/ha), while the average growth in Bupul village is as follows 31,08 cm (10 tonnes/ha), 30,89 cm (5 tonnes/ha), 23,52 cm ( 0 tonnes/ha).